ИЛМИЙ - ПЕДАГОГИК ВА ЎҚУВ – МЕТОДИК НАШРЛАР ОРҚАЛИ ИНФОРМАЦИЯВИЙ ТАҲДИДЛАРГА ҚАРШИ КУРАШИШ МЕХАНИЗМИ - Махмудов, С.Ю.; Умаралиева, М.А. (SCIENCE and SOCIETY, 2016)
The article deals with the problems of restoring information-related threats by means of scientific-pedagogical and educational publications. The authors offer recommendations on the organization of the system of publishing activities aimed at the prevention of the factors having a negative impact on moral education, culture and spirituality of the teaching community.